2011
DOI: 10.1007/s10753-011-9376-7
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-10 Gene Polymorphisms Are Associated with Type 2 Diabetes With and Without Nephropathy: A Study of Patients from the Southeast Region of Iran

Abstract: The impact of several environmental and genetic factors on diabetes and its complications is well documented. It has also been established that cytokines play a key role in the regulation of immune responses which have been shown to be important in the pathogenesis of diabetes. Studies showed that single-nucleotide polymorphisms within the -592 region of interleukin-10 (IL-10) are associated with the regulation of its expression. In this study, we aimed to find polymorphisms of this region that may be associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
(29 reference statements)
1
36
1
Order By: Relevance
“…IL-10 levels increased in IL-10-(−592C/C) genotype compared to IL-10-(−592A/A) and IL-10-(−592A/C) genotypes in DN patients while such difference was not found in T2DM patients without nephropathy. Similar to our findings, IL-10-(-592C/A) genotype distribution didn't differ between T2DM patients with or without nephropathy and IL-10 (-592C/A) genotype revealed significant association with cytokine expressions in DN patients [9,14,15]. Twenty-eight polymorphisms occur in the promotor region of IL-10 gene, these polymorphisms were found to affect gene transcription and expression.…”
Section: Discussionsupporting
confidence: 88%
“…IL-10 levels increased in IL-10-(−592C/C) genotype compared to IL-10-(−592A/A) and IL-10-(−592A/C) genotypes in DN patients while such difference was not found in T2DM patients without nephropathy. Similar to our findings, IL-10-(-592C/A) genotype distribution didn't differ between T2DM patients with or without nephropathy and IL-10 (-592C/A) genotype revealed significant association with cytokine expressions in DN patients [9,14,15]. Twenty-eight polymorphisms occur in the promotor region of IL-10 gene, these polymorphisms were found to affect gene transcription and expression.…”
Section: Discussionsupporting
confidence: 88%
“…Kung et al (2010) also reported a significant association between the -592A/C polymorphism in IL-10 and type 2 diabetic nephropathy, via altered IL-10 production. However, these results were not observed in two studies; that is, IL-10 polymorphisms were not correlated with susceptibility to type 2 diabetic nephropathy (Arababadi et al, 2012;Erdogan et al, 2012). In this study, we observed a significant correlation between the IL-10 -1082G/A polymorphism and the risk of diabetic nephropathy in a Chinese population.…”
Section: Discussioncontrasting
confidence: 84%
“…Several studies have also investigated the role of IL-10 polymorphisms in the development of diabetic nephropathy; however, the results of these studies are inconsistent (Babel et al, 2006;Ezzidi et al, 2009;Mtiraoui et al, 2009;Arababadi et al, 2012;Erdogan et al, 2012). Babel et al (2006) reported an association between the GG genotype of the IL-10 -1082G/A polymorphism and an increased susceptibility to end-stage renal disease in German patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is considered to be a polygenic disease. Many single nucleotide polymorphisms (SNPs), including those in cytokine genes such as TNF-α [5], IL-6 [6], IL-10 [7], adiponectin [7], and resistin [8,9] have been reported to increase the risk of developing T2D and obesity.…”
Section: Introductionmentioning
confidence: 99%